2018
DOI: 10.2196/10105
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Self-Care of Diabetic Foot Ulcers Through a Mobile Phone App: User-Centered Design and Evaluation

Abstract: BackgroundWithout effective self-care, people with diabetic foot ulcers (DFUs) are at risk of prolonged healing times, hospitalization, amputation, and reduced quality of life. Despite these consequences, adherence to DFU self-care remains low. New strategies are needed to engage people in the self-care of their DFUs.ObjectiveThis study aimed to evaluate the usability and potential usefulness of a new mobile phone app to engage people with DFUs in self-care.MethodsWe developed a new mobile phone app, MyFootCar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
122
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(126 citation statements)
references
References 46 publications
0
122
0
4
Order By: Relevance
“…This gap can be bridged through user-centered design approaches, where designers and users are brought together in the early system development phase to communicate directly. [24][25][26] User-centered design, however, can be time and resource consuming and is not always feasible for the development of interactive dashboards. This leads to inevitable differences in mental models that create usability issues and the need for comparing the mental models when examining underlying reasons for usability issues.…”
Section: Introductionmentioning
confidence: 99%
“…This gap can be bridged through user-centered design approaches, where designers and users are brought together in the early system development phase to communicate directly. [24][25][26] User-centered design, however, can be time and resource consuming and is not always feasible for the development of interactive dashboards. This leads to inevitable differences in mental models that create usability issues and the need for comparing the mental models when examining underlying reasons for usability issues.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a positive correlation between awareness levels and compliance among patients with diabetes; good disease awareness can improve a patient's treatment compliance, thus facilitating the patient's treatment . One study showed that the extended nursing model, based on applications, could effectively improve a patients' cognition of their own disease .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a positive correlation between awareness levels and compliance among patients with diabetes; good disease awareness can improve a patient's treatment compliance, thus facilitating the patient's treatment. 22,23 One study showed that the extended nursing model, based on applications, could effectively improve a patients' cognition of their own disease. 24 Continuous care for patients with type 2 diabetes using mobile health application could provide diversified health education, stable follow-up systems, and professional medical and resource supports, leading to improvements in patient cognition and improved selfmanagement.…”
Section: Continuous Care Based On Mobile Health Applicationmentioning
confidence: 99%
“…37 Patients also wished to receive feedback from the clinician through mHealth after sharing the information. 37 "Most participants were receptive to the idea of being able to communicate with and send physiological readings to their HCP via a mobile phone app. Specifically, they liked the idea of being able to send images of their feet or DFU and receiving an alert of its status."…”
Section: The Relationship With Hcpsmentioning
confidence: 99%
“…36 "Mum sent a copy because she wasn't able to get up to the hospital with me, my son sent one, my daughter sent one and there's so many copies in there, they're all out of sequence." 37…”
Section: The Role Of Wound Image Takingmentioning
confidence: 99%